2010
DOI: 10.5194/bg-7-387-2010
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of ground-based microorganisms on cloud formation in the atmosphere

Abstract: Abstract. The formation of clouds is an important process for the atmosphere, the hydrological cycle, and climate, but some aspects of it are not completely understood. In this work, we show that microorganisms might affect cloud formation without leaving the Earth's surface by releasing biological surfactants (or biosurfactants) in the environment, that make their way into atmospheric aerosols and could significantly enhance their activation into cloud droplets.In the first part of this work, the cloud-nuclea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 45 publications
(44 reference statements)
6
65
0
1
Order By: Relevance
“…Finally, these discrepancies in aerosol water uptake below and above water saturation have been observed in marine atmospheres Ovadnevaite et al, 2011). It has been hypothesized that the presence of biopolymers and biosurfactants in aerosol derived from sea-spray in biologically active waters contributes to this phenomena (O'Dowd et al, 2004;Ekström et al, 2010;Ovadnevaite et al, 2011).…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Finally, these discrepancies in aerosol water uptake below and above water saturation have been observed in marine atmospheres Ovadnevaite et al, 2011). It has been hypothesized that the presence of biopolymers and biosurfactants in aerosol derived from sea-spray in biologically active waters contributes to this phenomena (O'Dowd et al, 2004;Ekström et al, 2010;Ovadnevaite et al, 2011).…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Selective enrichment of specific surfactant materials -in the sea-surface microlayer and in atmospheric aerosolshas been well described (Barger and Garret, 1970;Mukerjee and Handa, 1981;Blanchard, 1990;Tseng et al, 1992;Oppo et al, 1999;Ekström et al, 2010). This enrichment of surfactants is even more increased at the sea surface during rough sea conditions, when wave breaking action causes air bubbles to be trapped beneath the water surface (O'Dowd and de Leeuw, 2007).…”
mentioning
confidence: 99%
“…E. coli and P. aeruginosa have been used as model microorganisms in studies dealing with primary biological aerosol particles (4). These bioaerosol particles have been proposed to act as cloud condensation nuclei (CCN) (6,15), suggesting a possible transfer of these opportunistic pathogens into rainwater through cloud droplets. Turkum et al (2008) suggested that most of the species found in rainwater were derived from aerosol and gasphase components (47).…”
Section: Resultsmentioning
confidence: 99%